Smart Specialization as a Comprehensive Territorial and Sectoral Approach to Determining Regional Development Priorities - STRYABKOVA, Elena Anatolievna; VLADYKA, Marina Valentinovna; LYSHCHIKOVA, Julia Vladimirovna; RZAYEV, Anar Yashar; KOCHERGIN, Mikhail Alexandrovich (Journal of Environmental Management and Tourism, 2021)
The relevance of the study is due to the active spread of the concept of smart specialization as a comprehensive territorial and sectoral approach to the development of territories not only in the EU but also in other countries, as well as the emergence of new directions and modifications. The article analyzes the ten-year evolution of the concept of smart specialization from a predominantly sectoral approach to a comprehensive balanced territorial-sectoral approach to determining the priorities for the development of regions based on unique competitive advantages based on entrepreneurial search in the context of interregional and macroregional interaction. The possibilities and prospects of using a smart specialization in the implementation of regional development policies of developing countries for the formation of innovative and technological industrial models of development and integration into global value chains have been evaluated. It has been established that at present the concept of smart specialization continues to develop and should consider such modern trends as technological connectivity of industries, digitalization, and convergence of technologies, blurring and increasing transparency of regional and state borders, glocalization, the development of interrelated processes of "competition", "co-evolution", and "co-specialization" of territories.